2016
DOI: 10.1016/j.clbc.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Interventions to Enhance Adherence to Hormone Therapy in Breast Cancer Survivors: A Systematic Literature Review

Abstract: Adjuvant hormonal therapy contributes to reductions in recurrence and mortality for women with hormone receptor positive breast cancer. However, adherence to hormonal therapy is suboptimal. This is the first systematic literature review examining interventions aimed at improving hormonal therapy adherence. Researchers followed the PRISMA guidelines. PubMed-Medline, CINAHL, PsychInfo, Ovid-Medline, and EMBASE were searched for behavioral interventions that aimed to enhance adherence to adjuvant hormonal therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(108 citation statements)
references
References 52 publications
4
103
1
Order By: Relevance
“…Differences between physicians and patients in perceptions of medicines may also pose important barriers to adherence: patients in 1 large AET study reported that an important barrier to continuing AET was "I was not sure if it (the medication) was helping," 35 and a meta-analysis of 5 randomized studies showed that educational interventions to address such issues had little impact on adherence. 36 Our study, therefore, adds a potential new target to otherwise disappointing efforts to improve adherence to oral cancer medications. A few studies outside oncology have examined whether improving synchronization can improve adherence.…”
Section: Discussionmentioning
confidence: 92%
“…Differences between physicians and patients in perceptions of medicines may also pose important barriers to adherence: patients in 1 large AET study reported that an important barrier to continuing AET was "I was not sure if it (the medication) was helping," 35 and a meta-analysis of 5 randomized studies showed that educational interventions to address such issues had little impact on adherence. 36 Our study, therefore, adds a potential new target to otherwise disappointing efforts to improve adherence to oral cancer medications. A few studies outside oncology have examined whether improving synchronization can improve adherence.…”
Section: Discussionmentioning
confidence: 92%
“…38 Assessing emotions towards AET in clinical practice could be an efficient strategy to identify women who may be less likely to adhere to AET. 30 Given the lack of success of most AET adherence interventions, 9 findings from this study can inform future interventions to target untapped psychosocial factors to enhance adherence to AET and survivorship.…”
Section: Discussionmentioning
confidence: 99%
“…Because psychosocial factors are modifiable, they are promising intervention targets. Interventions that promote AET adherence are limited . Utilizing conceptual models to examine the relationship between psychosocial factors and adherence increases their potential for informing the development of successful interventions .…”
Section: Introductionmentioning
confidence: 99%
“…Few interventions have been found to be effective for managing side effects for the duration of therapy. Some evidence suggests that tailored patient counseling, particularly for older adult survivors, may be initially beneficial to promoting adherence (Hugtenburg, Timmers, Elders, Vervloet, & van Dijk, 2013); however, in general, clinical interventions for medication adherence have not included behavioral approaches beyond reminder systems (Easthall, Song, & Bhattacharya, 2013; Hurtado-de-Mendoza, Cabling, Lobo, Dash, & Sheppard, 2016). Increasing knowledge of side effects, communicating the benefits of the prescribed medication to improve adherence motivation, and identifying opportunities to resolve barriers to medication use (such as side effects) have been highlighted in reviews as critical components in a long-term adherence model in clinical practice (Accordino & Hershman, 2013; DiMatteo, Haskard-Zolnierek, & Martin, 2012).…”
Section: Implications For Nursing and Intervention Opportunitiesmentioning
confidence: 99%